2019
DOI: 10.2147/rrcc.s182162
|View full text |Cite
|
Sign up to set email alerts
|

<p>Brugada syndrome: updated perspectives</p>

Abstract: Since the first reported descriptions of Brugada syndrome, there has been a growing awareness and appreciation of the disease and its implications. From the diagnostic criteria, to risk stratification and management, there is an ongoing evolution, reclassification and re-thinking of Brugada syndrome as basic science, registry and clinical trial data shape our understanding of the pathophysiology and its clinical implications. This in-depth review sheds light on the most important literature to date, highlighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Nevertheless, it is considered that a type 1 ECG solely, whether spontaneous or documented during a provocation test, is positive for BrS. Given the relative difficulty and absence of supporting evidence in its prognostic value, the Shanghai Score System has not yet achieved universal recognition; therefore, a large percentage of medical centers continue to diagnose BrS merely on a type 1 ECG in the absence of particular adjustable variables [ 25 ].…”
Section: Clinical Characteristics and Diagnostic Criteria Of Brsmentioning
confidence: 99%
“…Nevertheless, it is considered that a type 1 ECG solely, whether spontaneous or documented during a provocation test, is positive for BrS. Given the relative difficulty and absence of supporting evidence in its prognostic value, the Shanghai Score System has not yet achieved universal recognition; therefore, a large percentage of medical centers continue to diagnose BrS merely on a type 1 ECG in the absence of particular adjustable variables [ 25 ].…”
Section: Clinical Characteristics and Diagnostic Criteria Of Brsmentioning
confidence: 99%
“…Brugada syndrome is an arrhythmogenic cardiac manifestation first described in 1992, which is responsible for ventricular tachycardia and sudden death. The Shanghai Criteria has been proposed for the diagnosis of Brugada syndrome, usually in the presence of a type 1 ECG [20]. There is overlap with ACM considering the ventricular fibrotic changes, dilatation of RVOT, RV focal dyskinesia, and even the presence of common gene mutations (sodium channel 5A-SCN5A).…”
Section: Differential Diagnosis-pathologic Conditionsmentioning
confidence: 99%
“…There is overlap with ACM considering the ventricular fibrotic changes, dilatation of RVOT, RV focal dyskinesia, and even the presence of common gene mutations (sodium channel 5A-SCN5A). However, patients with Brugada syndrome do not exhibit global RV systolic dysfunction or global dilatation [20], and one study showed that only 8% presented LGE and none met rTFC 2010 [21].…”
Section: Differential Diagnosis-pathologic Conditionsmentioning
confidence: 99%
“…[78] The causes of Brugada syndrome include genetic, environmental, and hormonal components. [79] The most feasible mechanism for n-3 polyunsaturated fatty acids' anti-arrhythmic action is altering the cardiac ion channels. [80] The rapid sodium channel current is inhibited by n-3 polyunsaturated fatty acids, while the transient outward potassium current and the delayed outward potassium current are promptly activated.…”
Section: Role Of Polyunsaturated Fatty Acids In Brugada Syndromementioning
confidence: 99%